2009
DOI: 10.3109/07420520903221319
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality in Professional Ballet Dancers

Abstract: Ballet dancers are competitive athletes who undergo extreme physical and mental stress and work according to an irregular schedule, with long days of training, rehearsal, and performance. Their most significant potential risks entail physical injury and altered sleep. The elaborate training requirements for ballet dancers do not allow regular chronobiological patterns or a normal sleep-wake rhythm. Our aim was to investigate the sleep-wake rhythm and sleep quality during rehearsal phases prior to a ballet prem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
78
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(89 citation statements)
references
References 41 publications
7
78
1
3
Order By: Relevance
“…Aesthetic athletes such as gymnasts, professional dancers and synchronized swimmers train and compete in conditions of extreme physical and mental stress (Fietze et al, 2009); moreover, training hours are usually based on logistics rather than on physiological aspects of the human body. Thus, athletes cannot rest sufficiently, they have irregular chronobiological sleepwake rhythm (Fietze et al, 2009), low EA, unbalanced contribution of macronutrients, and micronutrients, stress and low BMI for their age (Silva & Paiva, 2014). In fact, Brand et al (2010b) found out that female athletes, who weekly spent 17.7 hours exercising, had a worse quality of sleep (5.2 ± 1.1) when compared with controls (4.9 ± 1.2).…”
Section: Discussionmentioning
confidence: 99%
“…Aesthetic athletes such as gymnasts, professional dancers and synchronized swimmers train and compete in conditions of extreme physical and mental stress (Fietze et al, 2009); moreover, training hours are usually based on logistics rather than on physiological aspects of the human body. Thus, athletes cannot rest sufficiently, they have irregular chronobiological sleepwake rhythm (Fietze et al, 2009), low EA, unbalanced contribution of macronutrients, and micronutrients, stress and low BMI for their age (Silva & Paiva, 2014). In fact, Brand et al (2010b) found out that female athletes, who weekly spent 17.7 hours exercising, had a worse quality of sleep (5.2 ± 1.1) when compared with controls (4.9 ± 1.2).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found that elite athletes have poor sleep quality [9,[15][16][17]. For example, more than 55% of athletes in the Bobsleigh Canada Skeleton team were flagged as being poor sleepers [9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, more than 55% of athletes in the Bobsleigh Canada Skeleton team were flagged as being poor sleepers [9]. Poor sleep was also observed in 50% of a sample of 24 professional ballet dancers [15], 50% of 175 elite rugby and cricket athletes [16], and 25% of 107 professional Finnish hockey athletes [18]. Despite such evidence for a high prevalence of poor sleep in elite athletes, little is known about what kinds of sleep disturbances occur.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the manner in which sleep duration and efficiency are affected by strenuous exercise and training days remains unclear (Fietze et al, 2009). Previous sleep research has primarily focused on physically active groups of 'good sleepers' whereby the exercise stress is low and the margin for sleep improvement is relatively small (ceiling effect) (Driver & Taylor, 2000).…”
Section: Introductionmentioning
confidence: 99%